2018
DOI: 10.1111/mmi.14096
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of PDC1, a novel protein involved in the epigenetic cell degeneration Crippled Growth in Podospora anserina

Abstract: The model fungus Podospora anserina exhibits Crippled Growth (CG), a cell degeneration process linked to the spreading of a prion-like hereditary element. Previous work has shown that the PaMpk1 MAP kinase and the PaNox1 NADPH oxidase are key player in setting up CG. Here, we identified PDC1, a new gene that negatively regulates the PaMpk1 pathway, by identifying the gene mutated in the PDC mutant. This mutant exhibits strong CG in conditions where the wild-type does not. PDC1 encodes a small protein conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In previous analyses [ 2 , 45 ], we positioned IDC proteins with respect to PDC1 by double mutant analysis. PDC1 encodes a repressor within the PaMpk1/PaNox1 pathway and is positioned between the PaMpk1/PaMpk2 MAP kinases and the other members of the cascade ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous analyses [ 2 , 45 ], we positioned IDC proteins with respect to PDC1 by double mutant analysis. PDC1 encodes a repressor within the PaMpk1/PaNox1 pathway and is positioned between the PaMpk1/PaMpk2 MAP kinases and the other members of the cascade ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…PDC1 encodes a repressor within the PaMpk1/PaNox1 pathway and is positioned between the PaMpk1/PaMpk2 MAP kinases and the other members of the cascade ( Figure 7 ). To position PaPro1 and IDC4 within the cascade, we constructed the PaPro1 Δ PDC1 Δ and IDC 508 PDC 2205 double mutants; PDC 2205 is a null allele of PDC1 [ 45 ]. Phenotypic analyses of these mutants ( Figure 8 ) showed that both lacked pigments, aerial hyphae and were female sterile, yet both developed CG sector on M2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation